The Application Of Marketing Content In Improving Customer Engagement Harlog Studio In The City Makassar - Lira, Darmais; Aslinda, Andi; Baharuddin, Aris (Universitas Negeri Makassar, 2025)
Application of Content Marketing to Increase Customer Engagement at HarlogStudio in Makassar City is one way to find out content marketing that can be used in running a business. The problem that arises is how to apply content marketing in increasing customer engagement and the determinant factors in its application.To achieve this goal, data collection techniques are used through observation, interviews, and documentation. The data is processed using a qualitative approach. This study took 5 (people) with representatives and met the criteria in this study. Source of data in this research is primary data. The interview technique was carried out in a structured manner using interview guidelines. The results of this study indicate that the application of content marketing in increasing customer engagement at Harlog Studio in Makassar City, namely business founders in marketing their product content can reach a wider audience and more consumers so that they are assisted by social media. The social media used are Instagram, Facebook, the YouTube platform and the official website page. Even though the application of content marketing at Harlog Studio has not been maximized, consumers who have used the service have covered the Makassar city area. Second, the supporting factors in the application of content marketing in increasing customer engagement are by utilizing social media to reach more consumers and facilitate promotion. Third, the inhibiting factor is that there is no schedule for posting content so that the available content has not been updated. Keywords: content marketing, digital marketing, customer engagement